Evidence of Place: Becoming a Region in Rural Canada. (27th November 2015) - Markey, Sean; Breen, Sarah‐Patricia; Vodden, Kelly; Daniels, Jen
Abstract: The purpose of this article is to investigate whether place is emerging in practice as a critical dimension in the development of Canadian rural regions. Recently, Jones and Paasi set regional researchers the task of better understanding how regions 'become'. In researching this question, we are particularly interested in the definition and expression of place‐based identity as a mobilizing force for regionalism. Our findings suggest that, while identity plays a critical role in fostering regional development processes, it is either too emergent or actively resisted within our research sites to be a significant force for place‐based regional development.